ANALYSIS OF USING MOTIFS IN THE DANIEL DERONDA BY GEORGE ELIOT - Akhmedova, Gavkharoy (Educational Research in Universal Sciences, 2023)
The novel Daniel Deronda is a literary fiction novel that encompasses other genres such as family drama and coming of age expanding peoples' overall psychology and thoughts. The author uses characters like George Eliot to show portray the positive manner and sensitivity of people.